Image structural classification technologies based on statistical analysis of descriptions in the form of bit descriptor set. - Gorokhovatskyi, V.; Gadetska, S.; Stiahlyk, N. (My University, 2020)
The problem of image recognition in computer vision systems is considered. We offer technologies for classifying visual objects using a statistical center based on a structural description of the image as a set of key point descriptors. The use of statistics for the bits of the description data helps to increase performance while providing sufficient classification performance. Results of experimental modeling and peculiarities of implementation of the developed approaches are discussed.
Keywords: computer vision; детектор BRISK